THE VALUE OF CROP ROTATION IN THE CULTIVATION OF VACCARIA HISPANICA IN CONDITIONS OF TYPICAL GRAY SOILS OF THE TASHKENT OASIS - Trobjon Makhkamov; Gulomjon Jumaboyev (American Journals, 2023)
In the world, great importance in production is attached to the intensification of the use of valuable plants, that is, the use of all parts of the plant for specific purposes. Vaccaria hispanica (Mill.) Rauschert is one of the promising plants grown in many countries of the world for the production of medicinal raw materials and saponins. Vaccaria hispanica is a promising medicinal plant of the Spanish millennium and, despite its wide distribution on the territory of our Republic, the possibility of obtaining raw materials is very small, and at the same time, many scientists consider it a plant with a high cultivation potential, so it is urgent to develop methods for growing raw materials in the soil. -climatic conditions of the Tashkent oasis. On the other hand, the development of scientifically substantiated optimal methods for propagating and growing the V. hispanica plant, the organization of industrial plantations, and the improvement of methods for preparing high-quality raw materials acquire scientific and practical importance.